A prospective pilot study of home monitoring in adults with cystic fibrosis (HOME-CF): protocol for a randomised controlled trial. Issue 1 (December 2017) - Choyce, Jocelyn; Shaw, Karen; Sitch, Alice; Mistry, Hema; Whitehouse, Joanna; Nash, Edward
Abstract Background Home monitoring has the potential to detect early pulmonary exacerbations in people with cystic fibrosis (CF), with consequent improvements in health outcomes and healthcare associated costs. This study aims to assess the effects of home monitoring on hospital admissions, quality of life, antibiotic requirements, exacerbation frequency, lung function, nutritional outcomes, anxiety, depression, costs and health outcomes, as well as the qualitative effects on the patient experience. Methods This randomised controlled mixed-methods trial aims to recruit 100 adults with CF cared for in one large regional CF centre. Participants are randomly allocated 1:1 to the intervention group (twice-weekly home monitoring of symptoms measured by the Cystic Fibrosis Respiratory Symptom Diary – Chronic Respiratory Infection Symptom Score (CFRSD-CRISS) and Forced Expiratory Volume in one second (FEV1 )) or a control group (routine clinical care) for the 12-month study period. Measurements are recorded at study visits at baseline, 3, 6, 9 and 12 months. Spirometry, body weight, co-morbidities, medications, hospital inpatient days, courses of antibiotics (oral and intravenous), pulmonary exacerbations (defined by the modified Fuchs criteria) are recorded at each study visit. Health status, capability and health economics are measured at each study visit by the Hospital Anxiety and Depression Scale (HADS), the ICEpop CAPability measure for Adults (ICECAP-A), EuroQol 5 dimensions (EQ-5D-5L) questionnaire and an adapted resource use questionnaire. The patient experience is assessed by semi-structured qualitative interviews at baseline and 12 months. Discussion Results from this study will help to determine the effect of home monitoring on inpatient bed days and quality of life in adults with CF, as well as other relevant health and health economic outcomes. Trial registration This study protocol is registered with Clinicaltrials.gov (NCT02994706 ), date registered 16th July 2014